Confidently beautiful a study of the image construction of a Miss University Beauty Queen on selected social media texts - Guino, Dave Merro 1996-; Olaguer-Ajibe, Ma. Amor; University of the Philippines. College of Mass Communication (2017)
"This study looks into how a beauty queen's image is constructed on social media texts. Specifically, it looks into how the image of a Miss Universe beauty queen, as projected by Pia Wurtzbach, is constructed on the Miss Universe Organization's official Facebook page. Furthermore, the goal of this study is to construct an image of a Miss Universe beauty queen based from the existing beauty queen ideals from the related literature, and the data gathered from the selected social media texts. This study will be employing textual analysis on selected photos and videos of Pia Wurtzbach in order to gather substantial data that would be associated with the image of a Miss Universe beauty queen. Semiotics of Rolan Barthes will be the theoretical guide of the study. Particularly, the two orders of signification of Barthes--namely, denotation and connotation -- will aid the deconstruction of the social media texts so that the different elements will be analyzed and interpreted according to the researcher's historical and cultural background. Using connotation, which involves deeper reading of the texts, underlying meanings and messages of the social media texts will be described. From these data, commonalities and patterns will be identified and classified accordingly based on the physical appearance and character in order to construct an image of a Miss Universe beauty queen. Furthermore, this study will be added to the roster of limited pageantry and social media studies."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Beauty contestants--Philippines.; Wurtzbach, Pia